PENERAPAN EAR TRAINING TERHADAP KEMAMPUAN INTONASI PADUAN SUARA MAHASISWA SENDRATASIK UNIVERSITAS NEGERI PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This research is motivated by the still varying intonation abilities of the members of the Padang State University Student Choir, so that efforts are needed to improve pitch accuracy through ear training. The purpose of this study is to describe the process of implementing ear training and see its impact on the members' intonation abilities. The method used in this study is qualitative with a descriptive approach, where data is obtained through observation, interviews, and documentation during eight practice sessions. The results of the study indicate that the implementation of ear training is carried out through five stages, namely sound presentation, listening to the sound, singing the sound, checking the sound, and repeating the sound. The practice process is also supported by using drill methods and peer tutors, as well as the Sibelius application as a learning aid. Through gradual and repeated practice, the members' intonation abilities show improvement, as seen from the reduction in pitch errors, increased voice stability, and growing confidence in singing. Therefore, the implementation of ear training has a positive impact on the quality of the choir members' intonation and can be used as an alternative method in choir learning.